2019
DOI: 10.1021/acs.orglett.9b00664
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Diastereoselectivity in a Masked Acyl Cyanide (MAC) Reaction: Synthesis of Protected erythro-β-Hydroxyaspartate Derivatives

Abstract: Using Garner’s aldehyde as a substrate, one-pot MAC hydroxyhomologation reactions proceeded in good yields and with anti selectivity for the first time (dr up to 9:1). The products were used to prepare a panel of protected derivatives of erythro-β-hydroxyaspartic acid and erythro-β-hydroxyasparagine as single enantiomers in a few steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Running the reaction at room temperature had a marginally negative effect on the yield (entry 10). For H-MAC-TBDPS 1c, a comparable reactivity profile was once again observed, with yields of 4c/4c′ ranging from 51 to 74% depending on the number of reagent equivalents (entries [11][12][13][14]. Running the reaction at room temperature had no perceptible effect on the yield (entry 15).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Running the reaction at room temperature had a marginally negative effect on the yield (entry 10). For H-MAC-TBDPS 1c, a comparable reactivity profile was once again observed, with yields of 4c/4c′ ranging from 51 to 74% depending on the number of reagent equivalents (entries [11][12][13][14]. Running the reaction at room temperature had no perceptible effect on the yield (entry 15).…”
Section: Resultsmentioning
confidence: 70%
“…11 Recently, however, we discovered that when Garner's aldehyde is used as the electrophilic partner the oxyhomologation gives the corresponding MAC reaction product with an anti diastereoselectivity. 12 One of the appealing features of MAC methodology is that the mild reaction conditions ensure that no erosion of the inherent enantiomeric composition of a chiral substrate is observed; 7m,8c this means that the oxyhomologation of a single Fig. 1 The proposed mechanism for the reaction of an H-MAC- [Si] reagent with a protected chiral α-amino aldehyde, highlighting two models that may govern the diastereoselectivity in the first step.…”
Section: Introductionmentioning
confidence: 99%
“…With α-substituted propanedinitriles secured, we focused our attention toward oxidative hydrolysis of the obtained molecules via an acyl cyanide intermediate. We found that the desired transformation was efficiently achieved by adding dropwise a solution of 1a in MeCN to a solution of 10.0 equiv of H 2 O 2 and 2.0 equiv of Cs 2 CO 3 in H 2 O, affording 2a in 81% yield. Following this procedure, other malononitriles 2b – n were converted into heptopyranuronic acids 3b – n in moderate-to-excellent yields with the exception of thioglycoside 2j , which resulted in a complex mixture of products possibly due to oxidation of the anomeric thioether group triggering the undesired reactions.…”
mentioning
confidence: 99%
“…A powerful strategy for identifying drug candidates includes late-stage divergent modifications of bioactive natural product skeletons . To highlight the potential of sugar-based α-substituted propanedinitriles in the diversity-oriented synthesis of 6dHep p derivatives, compound 2f was exposed to oxidative transformations through the intermediacy of acyl cyanide. As shown in Scheme , treatment of 2f with N -, O -, and S -nucleophiles under 1 atm of dioxygen atmosphere and 3.0 equiv of Cs 2 CO 3 in MeCN supplied the desired amides 4a – c , esters 4d – f , and thioesters 4g and 4h in 40–93% yields. Access to 4b and 4g provides an attractive avenue to sugar-derived ketones relying on either nucleophilic addition of organomagnesium and organolithium reagents to Weinreb’s amides or Liebeskind–Srogl cross-coupling reaction of arylthio esters with aryl boronic acids.…”
mentioning
confidence: 99%
“…Although there are several strategies reported to construct HyAsp, few of them could be conveniently utilized to prepare suitable building blocks for this synthetic route. This includes the tedious route starting from tartaric acid, [8] non‐suitable side chain protection in the masked acyl cyanide reaction [9] and difficult observation of trans product in the Sharpless aminohydroxylation reaction [10] . Inspired by the Sardina's work, [11] herein we developed a concise synthetic route for selectively preparing 2 a or 2 b in five steps with 37–40 % overall yield (Scheme 1.…”
Section: Figurementioning
confidence: 99%